2017
DOI: 10.1292/jvms.17-0359
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of <i>Toxoplasma gondii</i> in free-ranging and feral cats on Amami Oshima Island, Japan

Abstract: On Amami Oshima Island, free-ranging and feral cats are harmful to wildlife populations. In this study, the seroprevalence of Toxoplasma gondii in these cats was examined using a newly developed Gaussia luciferase immunoprecipitation system assay. Of 1,363 cats, 123 cats (9.0%) was positive for T. gondii. The prevalence was significantly different in different areas; among cats in the rural area, where many wild animals live, including endangered species, T. gondii infection was more prevalent than in the urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…An estimated 600–1,200 feral cats roam the forested areas of the Amami-Oshima Island (Shionosaki, 2016). In an epidemiological study in the Amami-Oshima Island, seroprevalence of T. gondii among outdoor cats in these mountain areas was shown to be higher than that in urban areas (Matsuu et al, 2017). Furthermore, in such natural areas, the Amami spiny rat, Ryukyu long-furred rat, and Amami rabbit are known to be important prey species for feral cats (Shionosaki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 600–1,200 feral cats roam the forested areas of the Amami-Oshima Island (Shionosaki, 2016). In an epidemiological study in the Amami-Oshima Island, seroprevalence of T. gondii among outdoor cats in these mountain areas was shown to be higher than that in urban areas (Matsuu et al, 2017). Furthermore, in such natural areas, the Amami spiny rat, Ryukyu long-furred rat, and Amami rabbit are known to be important prey species for feral cats (Shionosaki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of T. gondii in wildlife is correlated with the presence of final hosts since they contribute to environmental contamination via the excretion of oocysts in their feces (Lehrer et al, 2010; Fredebaugh et al, 2011). Recently, T. gondii antibodies were detected in 9.0% of feral and stray cats in Aammi-Oshima Islands (Matsuu et al, 2017), which indicated a potential risk of T. gondii transmission to endemic mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Mongoose generally feeds on small mammals such as rodents, birds, amphibians and reptiles. T. gondii infection found in this alien species indicates the predation of infected mice or ingestion of oocysts excreted in feces of domestic/feral cats [12]. The population of feral cats is increasing on Amami-Oshima Island, and they act as predators for certain endangered endemic species such as the Amami rabbit (Pentalagus furnessi), the Ryukyu long-tailed giant rat (Diplothrix legata) and the Amami spiny rat (Tokudaia osimensis) which are all Natural monument of Japan [19].…”
mentioning
confidence: 88%
“…Presumably, T. gondii can be transmitted among domestic/feral cats, the small Indian mongoose, and some endemic mammals on the island. Although the history of introduction of cats into Amami-Oshima Island is not well known, T. gondii infection found in wild small Indian mongooses indicates that domestic/feral cats spread this zoonotic pathogen on the island where wild cat species do not exist [12].…”
mentioning
confidence: 99%
“…The seropositivity rates have been reported in cats that visited animal hospitals; 5.4% (78/1,477) in cats from 17 prefectures (Hokkaido, Miyagi, Niigata, Ishikawa, Tochigi, Saitama, Kanagawa, Shizuoka, Aichi, Kyoto, Osaka, Hyogo, Shimane, Tokushima, Saga, Kagoshima, Okinawa) in 1994 and 1999 [11], and 6.0% (48/800) in those from 16 prefectures (Hokkaido, Gunma, Saitama, Tokyo, Kanagawa, Gifu, Aichi, Mie, Kyoto, Osaka, Tottori, Okayama, Hiroshima, Ehime, Fukuoka, Kumamoto) in 1997 [15]. The seroprevalence in free-ranging cats in Japan were reported as 9% in 2013-2017 in Amami Oshima Island [12], and 13.4% in 1998-1999 in Chiba prefecture [6]. In Tokachi subprefecture, Hokkaido in 2013-2014 showed significantly higher seroprevalence in cats allowed to roam outdoors or reared at the farm (30.0%) than in cats reared indoors (7.5%) [17].…”
mentioning
confidence: 96%